Optimization of selected casting parameters on the mechanical behaviour of Al 6061/glass powder composites. Issue 5 (May 2022) - Akinwande, Abayomi A.; Adediran, Adeolu A.; Balogun, Oluwatosin A.; Yibowei, Moses Ebiowei; Barnabas, Abel A.; Talabi, Henry K.; Olorunfemi, Bayode J.
Abstract: Aluminum alloy and its composites have versatile applications and can be produced via a cost-effective stir casting technique. However, stir casting is faced with some challenges including segregation, occurrence of intermetallic phases, agglomeration, and inducement of residual stress. In view of minimizing these defects, casting should be done applying optimal parameters that will yield the desired outcome. The present study focused on the optimization of stirring parameters of temperature, speed, and time in the production of Al 6061/glass powder composite. Evaluated responses are tensile strength, compressive strength, impact strength, and hardness. The results showed that the process parameters had statistical significance on all properties at 95 % confidence level. Combined interactions of these parameters also presented significant effects on the property responses. Optimum setting for process factors as regards tensile strength were evaluated to be 600 °C, 400 rpm, and 30 min for temperature, speed, and time, respectively. For compressive strength, it is 600 °C, 500 rpm, and 30 min; for hardness, the optimum settings are 700 °C, 400 rpm, and 30 min, while in the case of impact strength, the optimum settings are 500 °C, 400 rpm, and 30 min respectively. Optimization of the combined characteristics was obtained at the optimum conditions of 500 °C, 400 rpm, and 30 min for stirring temperature, speed, and time. Moreso, the significance of the parameters on the composite in descending order is temperature, time, and speed. Abstract : Al 6061, Composites, Glass powder, Optimization, Taguchi analysis.